Implementasi Pembayaran Zakat Emas Di Nagari Bangko Kecamatan Renah Pembarap - Risnawati, Melia; IKhwan; Zulfan (LPPM IAIN Sorong, 2024)
This research aims to understand further how gold zakat payments that do not comply with the haul (time requirements) in Nagari Bangko, Renah Pembarap District, are a problem that requires serious attention. This article analyzes various factors that cause this discrepancy, including a lack of understanding of the concept of zakat and administrative obstacles. The method used is qualitative, using data collection techniques through literature studies and interviews with local communities. Through this case study, this article also highlights the social and economic consequences of non-haul implementation. In addition, this article emphasizes the importance of education, better understanding of zakat regulations, and administrative improvements to ensure the effectiveness and sustainability of the gold zakat program in Nagari Bangko. Thus, collaboration between zakat institutions, the government and local communities is key in resolving this challenge and increasing the benefits felt by the community. The author draws conclusions. In the context of implementing gold zakat payments in Nagari Bangko, Renah Pembarap District, it can be concluded that this step is not only an effort to fulfill religious obligations, but is also an important instrument in building the social and economic sustainability of the local community. Through effective gold zakat management, society can experience increased prosperity and strengthen social ties within the community.